Temperature stable Sm(Nb1−xVx)O4 (0.0 ≤ x ≤ 0.9) microwave dielectric ceramics with ultra-low dielectric loss for dielectric resonator antenna applications. Issue 31 (16th July 2021) - Wu, Fang-Fang; Zhou, Di; Du, Chao; Sun, Shi-Kuan; Pang, Li-Xia; Jin, Biao-Bing; Qi, Ze-Ming; Varghese, Jobin; Li, Qiang; Zhang, Xiu-Qun
Abstract : A temperature-stable Sm(Nb0.8 V0.2 )O4 (SNV-0.2) microwave dielectric ceramic with ultra-low dielectric loss was fabricated, and an RDRA was designed for 5G mm-wave application for the first time, which is a good candidate for 5G and future millimeter-wave MIMO antenna applications. Abstract : Herein, the structure and dielectric properties of Sm(Nb1− x V x )O4 (SNV- x ) (0.0 ≤ x ≤ 0.9) ceramics were studied by crystal structure refinement, Raman, transmission electron microscope (TEM), far-infrared/THz reflectivity spectroscopy and microwave dielectric tests. Three kinds of ultra-low dielectric loss and temperature-stable Sm(Nb1− x V x )O4 (0.2 ≤ x ≤ 0.4) ceramics with permittivities of 18.01–16.89, Q × f values of 97 800–75 200 GHz (@∼8.6 GHz), and TCF of −5.6 ( x = 0.2), to +2.3 ppm °C −1 ( x = 0.3), then −6.3 ( x = 0.4) ppm °C −1 were synthesized in this system. It was found that V 5+ substitution can reliably induce the phase transition of monoclinic fergusonite (M-fergusonite, I 2/ a ) to tetragonal zircon phase (T-zircon, I 41 / amd ) ( x ≈ 0.3), while effectively reducing the phase transition temperature. TEM shows that there were two different orientation domain structures in the M-fergusonite phase, and the widths of the two domain structures get closer with an increase in B-site substitution. Moreover, the variations in permittivity ( ε r ), quality factor ( Q × f ), and the temperature coefficient of resonance frequency (TCF) were strongly related to the crystal distortion and phase transition. Notably, a rectangular dielectric resonator antenna (RDRA) was fabricated with an Sm(Nb0.8 V0.2 )O4 (SNV-0.2) specimen. The antenna resonated at 27.04 GHz and had a bandwidth of ∼820 MHz ( S 11 < −10 dB). This system is a good candidate for 5G and future millimeter-wave applications.